Parâmetros Curriculares Nacionais para o ensino médio: a perspectiva dos professores - Gomes, Anderson Severiano (2006)
The present research study aimed to investigate how the teachers of a public High School located on the periphery of the city of São Paulo conceive the curriculum reforms introduced in that teaching level from the 1990s onwards, specially the National Curriculum Parameters for High Schools (in Portuguese, PCNEM). The introductory part of the thesis discusses the educational reforms of this period based on the pertinent literature, which situates them in the context of the economic and cultural globalization processes. The text recovers and comments on the justifications used for the reformulations proposed for the High School curriculum, based on new learning paradigms marked by the demands brought by the changes that have occurred in the organization of the capitalist production and in the labor market. The school where the research was conducted, Escola Pública Estadual Angelópolis, is characterized through its history in the neighborhood and its leading role in the schools network of the state of São Paulo. The work environment of the teachers, the main subjects of the study, is also described. Nine teachers were interviewed, four of them in individual interviews and five in a. collective interview. In the period of one month, the researcher made observations inside the school. In their individual and collective interviews, the teachers reveal their difficulties, perplexities, anguishes and hopes concerning their work at school, showing the distance between the official curriculum proposals and the real work conditions that they face in their daily routine. To a certain extent, there are many convergence points with many PCNEM proposals; however, the teachers manifest other concerns that are not approached by this document, regarding the life conditions of the population of youths who attend the school and their limited perspectives of continuing their education and of being inserted in the labor world. In this context, the teachers oscillate between conformism and change. The study shows that the document of the Ministry of Education still needs to be fully understood, but that it alone will not solve the problems of the public High School. To achieve this, a more articulated action of all the actors, specially the teachers, is needed (among other factors of a more general nature), so as to create conditions to solve some problems experienced in the school dynamics, aiming to put into practice a curriculum that is restless, plural, inclusive and participative